2021
DOI: 10.1101/2021.03.24.436773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep learning-based chest X-ray age serves as a novel biomarker for cardiovascular aging

Abstract: Chest X-ray (CXR) is one of the most commonly performed medical imaging tests. Although aging, sex and disease status have been known to cause changes in CXR findings, the extent of these effects has not been fully characterized. Here, we present a deep neural network (DNN) model trained using more than 100,000 CXRs to estimate the patient's age and sex solely from CXRs. Our DNN exhibited high performance in terms of estimating age and sex, with Pearson's correlation coefficient between the actual and estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Some studies have reported age estimation from CXR images [ 39 ]. Hirotaka reported that the top of the mediastinum helps in predicting patients’ age [ 14 ]. Their results were similar to our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have reported age estimation from CXR images [ 39 ]. Hirotaka reported that the top of the mediastinum helps in predicting patients’ age [ 14 ]. Their results were similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CXR-age derived from chest radiographs may be of potential use as an imaging biomarker to represent the condition of the thorax. In fact, there have been emerging studies using CXR-age to successfully predict longevity, mortality, and cardiovascular risk [ 13 , 14 , 27 ], which provides a sound base for the imaging biomarker hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient age and gender are predicted from a proprietary dataset with a CNN in [22], with Grad-CAM [20] used to visualise characteristic features. Recent work has shown that overestimated patient age is predictive of cardiovascular and all-cause mortality rates [8,16]. GANs [5] have previously been used in a variety of medical image processing applications [23].…”
Section: Introductionmentioning
confidence: 99%